2022
DOI: 10.1007/s00345-022-04156-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in renal function after nephroureterectomy for upper urinary tract carcinoma: analysis of a large multicenter cohort (Radical Nephroureterectomy Outcomes (RaNeO) Research Consortium)

Abstract: Purpose To investigate prevalence and predictors of renal function variation in a multicenter cohort treated with radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). Methods Patients from 17 tertiary centers were included. Renal function variation was evaluated at postoperative day (POD)—1, 6 and 12 months. Timepoints differences were Δ1 = POD-1 eGFR − baseline eGFR; Δ2 = 6 months eGFR − POD-1 eGFR; Δ3 = 12 months eGFR − 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These findings were partially confirmed later by a multicenter study conducted by the RaNeO research consortium [61], where the presence of hydronephrosis was associated with lower renal function reduction. A possible explanation of this phenomenon could rely on the fact that established contralateral compensatory kidney hypertrophy of the ipsilateral urinary tract facilitates the compensatory role of the remnant solitary kidney.…”
Section: Renal Functional Outcomesmentioning
confidence: 59%
See 1 more Smart Citation
“…These findings were partially confirmed later by a multicenter study conducted by the RaNeO research consortium [61], where the presence of hydronephrosis was associated with lower renal function reduction. A possible explanation of this phenomenon could rely on the fact that established contralateral compensatory kidney hypertrophy of the ipsilateral urinary tract facilitates the compensatory role of the remnant solitary kidney.…”
Section: Renal Functional Outcomesmentioning
confidence: 59%
“…On the other hand, recent evidence suggests that preoperative eGFR ≤60 might have a negative impact on renal function recovery [ 62 , 63 ]. Moreover, a detrimental effect of postoperative acute kidney injury on eGFR can still be recognized at 6 and 12 months after surgery [ 61 ].…”
Section: Renal Functional Outcomesmentioning
confidence: 99%
“…In all patients, the median eGFR was 14.7 mL/min/1.73 m 2 lower from the preoperative period to the one-month postoperative period, and 23% of patients had an eGFR ≥ 50 at one month postoperatively. Previous studies demonstrated that the eGFR after RNU decreased at approximately 11.2-14.0 mL/min/1.73 m 2 compared to that preoperatively [ 5 , 8 - 10 ]. However, these reports differ in the timing of postoperative renal function evaluation, often after three months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Amirian et al [ 14 ] reported that in the ureter, locally advanced tumors theoretically penetrate the muscularis propria, potentially diminishing peristaltic activity, and thus causing obstruction, with HN being the result. In another study, the renal function of patients with UTUC with HN decreased only 5.5 mL/min/1.73 m 2 between the pre- and postoperative periods [ 8 ]. Our study showed that the eGFR of elderly patients with HN declined only to 8.3 mL/min/1.73 m 2 between the preoperative period and the one-month postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 50% of patients are not eligible for platinum-based chemotherapy due to postoperative renal failure. Therefore, patients are at high risk of postoperatively reduced renal function and it is recommended that neoadjuvant chemotherapy be considered ( 34 ). At present, the relative efficacy of adjuvant radiotherapy in SUC cases remains to be established.…”
Section: Discussionmentioning
confidence: 99%